Shelter from the Machine : Homesteaders in the Age of Capitalism - Strange, Jason G. (Book collections on Project MUSE., 2020)
"'You're either buried with your crystals or your shotgun.' That laconic comment captures the hippies-versus-hicks conflict that divides, and in some ways defines, modern-day homesteaders. It also reveals that back to-the-landers, though they may seek lives off the grid, remain connected to the most pressing questions confronting the United States today. Jason Strange shows where homesteaders fit, and don't fit, within contemporary America. Blending history with personal stories, Strange visits pig roasts and bohemian work parties to find people engaged in a lifestyle that offers challenge and fulfillment for those in search of virtues like self-employment, frugality, contact with nature, and escape from the mainstream. He also lays bare the vast differences in education and opportunity that leave some homesteaders dispossessed while charting the tensions that arise when people seek refuge from the ills of modern society -- only to find themselves indelibly marked by the system they dreamed of escaping"--